Differential HLA Association of GAD65 and IA2 Autoantibodies in North Indian Type 1 Diabetes Patients - Neihenuo Chuzho; Neeraj Kumar; Neetu Mishra; Nikhil Tandon; Uma Kanga; Gurvinder Kaur; Paras Singh; Gunja Mishra; Shreya Sharma; Narinder K. Mehra (Journal of Diabetes Research)
The human leucocyte antigen (HLA) association with type 1 diabetes (T1D) is well known but there are limited studies investigating the association between β-cell autoantibodies and HLA genes. We evaluated the prevalence of GAD65 and IA-2 autoantibodies (GADA and IA2A) in 252 T1D patients from North India and investigated the genetic association of GADA and IA2A with HLA class I and class II genes/haplotypes. GADA and IA2A were detected in 50.79% and 15.87% of T1D patients, respectively, while only 8.73% had both GADA and IA2A. HLA-DRB1∗03 was observed to be significantly higher in GADA+ T1D patients as compared to GADA– (91.41% vs. 66.13%, Bonferroni-corrected P Pc=1.11×10−5; OR=5.45; 95% CI: 2.67-11.08). Similarly, HLA-DQB1∗02 was found to be significantly increased in GADA+ patients (94.53%, Pc=2.19×10−5; OR=6.27; 95% CI: 2.7-14.49) as compared to GADA– (73.39%). The frequencies of HLA-DRB1∗04 and DQB1∗03 were increased in IA2A+ patients (45.0% and 52.5%, respectively) as compared to that in IA2A– (25.94% and 33.96%, respectively). Further, the frequency of DRB1∗03-DQB1∗02 haplotype was found to be significantly increased in GADA+ T1D patients as compared to GADA- (60.55% vs. 41.94%, P=3.94×10−5; OR=2.13; 95%CI=1.49-3.03). Similarly, HLA-DRB1∗04-DQB1∗03 haplotype was found to be significantly increased in IA2A+ T1D patients compared to IA2A– patients (22.5% vs. 12.97%; P=0.041; OR=1.95; 95%CI=1.08-3.52). None of the HLA class I genes (HLA-A, B, and Cw) was found to be associated with GADA or IA2A in people with T1D. Our findings suggest that HLA-DRB1∗03/DQB1∗02 and HLA-DRB1∗04/DQB1∗03 might play an important role in the development of GADA and IA2A, respectively.